Usulan Rute Pendistribusian Gas LPG Menggunakan Algoritma Dijkstra dan Algoritma Genetika Pada Model CGVRP - Oktaviani, Putri; Dalnis, Intan Permata; Wirdianto, Eri (Universitas Katolik Parahyangan, 2025)
Determining the route of distribution of goods for companies is an important aspect to consider. The distribution of 3 kg LPG gas at one of the companies in Bandung City does not yet have an optimal route. However, in previous research, a shorter route has been obtained with the Sweep algorithm, which is 118.85 km. The research continued using the Cluster Generalized Vehicle Routing Problem (CGVRP) model with the Dijkstra and Genetics algorithms. CGVRP is the determination of the shortest route using customer clusters. Dijkstra's algorithm is the determination of the route between 2 points from the starting point to the destination point. The result of the distance calculation with the Djkstraa algoritma is 114.779 km. Genetic Algorithm is the determination of the shortest route by reducing the attributes that are less dominant. The result of the distance calculating with Genetic Algorithm is 112 km. This shows a reduction in the total distribution mileage of 6.85 km compared to the completion of the Sweep algorithm in previous studies. The amount of this reduction is large enough to save the company's costs by 5.76%.